Early diarrhoea under sorafenib as a marker to consider the early migration to second‐line drugs. Issue 6 (6th July 2021) - Díaz‐González, Álvaro; Sapena, Víctor; Boix, Loreto; Torres, Ferrán; Sanduzzi‐Zamparelli, Marco; Da Fonseca, Leonardo G.; LLarch, Neus; Iserte, Gemma; Guedes, Cassia; Muñoz‐Martínez, Sergio; Darnell, Anna; Belmonte, Ernest; et al.
Abstract: Background: Despite atezolizumab and bevacizumab (A + B) is currently the first‐line treatment for hepatocellular carcinoma (HCC) patients, some patients will not be adequate for this combination. In the setting of sorafenib some adverse events have been proposed as prognostic factors. Objective: To characterize the early diarrhoea development as prognostic factor in 344 HCC patients. Methods: The development of early diarrhoea in sorafenib treatment defined as patients who developed diarrhoea and needed dose modification within the first 60 days of treatment (e‐diarrhoea) and 3‐grouping variables were analysed: Patients with e‐diarrhoea, patients who developed diarrhoea after the first 60 days of treatment (L‐diarrhoea) and patients that never developed diarrhoea (never diarrhoea). Results: The median overall survival in sorafenib treated patients was significantly different across groups (6.8 months for e‐diarrhoea, 26.7 months for L‐diarrhoea and 13.3 months for never‐diarrhoea). The emergence of e‐diarrhoea was associated with poor outcomes (hazard ratio [HR] 1.84 [95%CI 1.15–2.95]), while there was no increased/decreased risk of dismal evolution in patients with L‐diarrhoea (HR 0.66 [95%CI 0.42–1.03]). Conclusion: The emergence of e‐diarrhoea in HCC patients treated with sorafenib is an early predictor of dismal evolution under this therapy. Thus, prompt identification of these non‐responders may be useful for an early switch to second‐line therapies. Abstract :